[Landmannalaugar Area From Above] - Streng, Evelyn Fiedler (1975)
Photograph of the Landmannalaugar area from above. Rounded, brown mountains dotted sparsely with white snow sit on the shore ahead. A large blue lake stretches across the foreground, a small island and rocky offshoots sitting in the water on either side of the photograph. Two people stand along the bottom of the photograph with their hands cupped around their eyes as the look out at the landscape.